2012
DOI: 10.1515/secm-2011-0139
|View full text |Cite
|
Sign up to set email alerts
|

Effect of particle size on mechanical properties and tribological behaviour of aluminium/fly ash composites

Abstract: In the present study, aluminium alloy (A380) composites containing 3, 6, 9 and 12 weight percentage of fl y ash particles were fabricated by liquid metallurgy technique. Three different size ranges of fl y ash particles (50 -75 μ m, 75 -103 μ m and 103 -150 μ m) were used. The composites were evaluated for hardness, tensile strength, density, dry sliding wear and frictional behaviour. Pin-on disc apparatus was used to conduct wear tests at loads of 20, 30 and 40 N at a sliding speed of 3 m/s for a constant per… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 13 publications
(20 reference statements)
0
19
0
Order By: Relevance
“…It has been indicated that the coefficient of friction of the composites decreased with increase in the volume fraction of reinforcements [25,26,50,67,68]. The coefficient of friction of aluminum matrix composite reinforced with CNTs decreases with increasing volume fraction of CNTs in the composite as shown in Fig.…”
Section: Volume Fractionmentioning
confidence: 90%
See 1 more Smart Citation
“…It has been indicated that the coefficient of friction of the composites decreased with increase in the volume fraction of reinforcements [25,26,50,67,68]. The coefficient of friction of aluminum matrix composite reinforced with CNTs decreases with increasing volume fraction of CNTs in the composite as shown in Fig.…”
Section: Volume Fractionmentioning
confidence: 90%
“…It has been reported that an increase in the sliding speed causes an increase in the wear rate and decrease in the wear resistance of the MMCs [14,26,96,105], and the variation between the wear rate and sliding speed is usually linear [106,107]. As the sliding speed increases, the interface temperature also increases resulting in (a) the microthermal softening of matrix material [108], (b) oxide formation on the contact area [109], and (c) decrease in flow stress of the material [109].…”
Section: Sliding Speedmentioning
confidence: 99%
“…Anilkumar et al [15] have chosen Al 6061 alloy as the matrix material and fly ash with varying weight percentage (10%, 15%, 20%) with particle size [of 4-25, 45-50, 75-100 μm] as the reinforcement to produce the composite by stir casting. By analyzing the sample, the hardness, tensile strength, compressive strength increases with increase in weight fraction of fly ash.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Firstly, from the chemical point of view, functional bond owned by high dispersibility nano-silica powder modified by silane coupling agent KH570 connected inorganic nano-silica particles and Brought to you by | University of California Authenticated Download Date | 6/10/15 2:27 AM organic macromolecules of UPR. It resulted in an increase of the intermolecular binding force [8,9]; secondly, from the microscopic interface mechanics point of view, there existed flexible interface layer between two-phase interface which transferred the stress effectively and enabled propagation of the blocked micro-crack [10]; thirdly, from the crystallography point of view, high dispersibility nanosilica powder played the fine grain strengthening role in the UPR matrix because the nano-silica powder resulted in improving the crystal nucleation rate and reducing the UPR matrix crystallinity and grain size [11]. At the base of the above three reasons, the enhancement of the strengthening and toughening performance of nano-silica/UPR polymer composite was apparent.…”
Section: Influence Of High Dispersibility Nanosilica Powder On Upr Mamentioning
confidence: 99%